Diglossia in Arab Cinema: Language Strategies and Ideological Meanings in the Film Al-Irhāb wa al-Kabāb - Rofi’, Moh ‘Affan (Proceedings of International Conference on Islamic Civilization and Humanities, 2026)
Diglossia in Arabic-language films is a topic that has rarely been studied in depth, even though films have great potential to reflect how language choices can illustrate power and ideology. This study highlights the phenomenon of diglossia in the Egyptian satirical film Al-Irhāb wa al-Kabāb (Terrorism and Kebab, 1992) by director Sherif Arafa, exploring how the use of Fuṣḥā (Standard Arabic) and ʿāmmiyyah (colloquial Arabic) not only serves as a tool for communication but also conveys profound political messages. This study employs a qualitative descriptive approach with sociolinguistic analysis of key dialogues between community figures and government officials at the Mugamma Building in Cairo, selected through purposive sampling. The findings reveal that the shift in language within the film serves as a critical tool to satirize rigid political structures and bureaucracy. The fuṣḥā used by officials reflects the communication gap between the state and the people, while the ʿāmmiyyah used by the main character and the hostages radiates solidarity, honesty, and resistance. The symbol of “kebab” in the film’s narrative is positioned as an expression of the struggle for justice for the lower-middle class. Through the combination of high and low language, the film creates a powerful representation of the social and political turmoil in Egypt at the time.